2020
DOI: 10.3233/wor-203174
|View full text |Cite
|
Sign up to set email alerts
|

Graded exercise therapy does not restore the ability to work in ME/CFS – Rethinking of a Cochrane review

Abstract: BACKGROUND: Cochrane recently amended its exercise review for Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) in response to an official complaint. OBJECTIVE: To determine if the amended review has addressed the concerns raised about the previous review and if exercise is an effective treatment that restores the ability to work in ME/CFS. METHOD: The authors reviewed the amended Cochrane exercise review and the eight trials in it by paying particular interest to the objective outcomes. We also summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 95 publications
0
12
1
Order By: Relevance
“…Data from eight randomized clinical trials concluded that physical therapy improves exhaustion, quality of sleep, and health status of the patients in the long term, thus showing beneficial potential [ 12 ]. This finding contradicts the widespread opinion that patients always feel uncomfortable after physical exertion, a phenomenon known as PEM [ 115 ]. One of the aims of CFS treatment is the prevention of depression and suicidal tendencies by managing the physical and emotional issues resulting from ME/CFS [ 3 ].…”
Section: Resultscontrasting
confidence: 61%
“…Data from eight randomized clinical trials concluded that physical therapy improves exhaustion, quality of sleep, and health status of the patients in the long term, thus showing beneficial potential [ 12 ]. This finding contradicts the widespread opinion that patients always feel uncomfortable after physical exertion, a phenomenon known as PEM [ 115 ]. One of the aims of CFS treatment is the prevention of depression and suicidal tendencies by managing the physical and emotional issues resulting from ME/CFS [ 3 ].…”
Section: Resultscontrasting
confidence: 61%
“…In work and educational institutions, the lack of understanding and provision for people with CFS/ME creates obstacles for people with the illness to remain in those environments. CBT and GET do not restore the ability of a person with CFS/ME to work [47]. People with CFS/ME who cannot remain in employment need to access the benefits system.…”
Section: Discussionmentioning
confidence: 99%
“…As found by the reanalysis of the amended Cochrane exercise review (Vink and Vink-Niese, 2020), analysis of objective outcomes from three CBT and GET trials for ME/CFS confirmed the unreliability of subjective outcomes in non-blinded studies, as shown by the following examples:…”
mentioning
confidence: 68%